ANALISIS KESESUAIAN MATERI DAN LATIHAN SOAL PADA BUKU NETZWERK A1 DENGAN KOMPETENSI INTI DAN KOMPETENSI DASAR KURIKULUM 2013 KELAS X - Fauziyah Ruhyana; Amir Amir; Hafdarani Hafdarani (Allemania, 2023)
Textbooks are included in the supporting components in learning, therefore textbooks have a very important role in realizing education in accordance with the Core Competencies and Basic Competencies of the 2013 Curriculum in the 10th grade. Core Competencies and Basic Competencies in the 2013 Curriculum are a reference in making material and practice questions in textbooks, so that learning in schools is in accordance with the standards set by the government. However, not all textbooks are in accordance with the standards and needs of each level of learners. Research onÂ  textbooks was conducted to determine the suitability of the content of the Netzwerk A1 Kursbuch textbooks with the Core Competencies and Basic Competencies of the 2013 Curriculum for class X. The textbook used as research material or the corpus in this research is the Kursbuch Netzwerk A1 book. The purpose of this study is to describe the suitability of the material in the Netzwerk A1 book with Core Competencies and Basic Competencies for 10th grade class and describe the suitability of practice questions in the Netzwerk A1 book with Core Competencies and Basic Competencies for 10th grade class. The method used in this research is descriptive analysis. The data analysis technique in this research is content analysis using documentation studies to collect data in the form of material and practice questions in the Kursbuch Netzwerk A1 book. After collecting the data, then the data is analyzed for compatibility with the Core Competencies and Basic Competencies of 10th grade class. The results of the analysis showed that the Kursbuch Netzwerk A1 book is not all in compatible with the Core Competencies and Basic Competencies of 10th grade class, because the scope of the Kursbuch Netzwerk A1 book is still too broad to be a supporter of learning for 10th grade students. Based on the data obtained, there are 71 materials with 21 data or 29.60% in accordance with 18 materials in 1st semester and 3 materials in 2nd semester relevant, 11 data or 15.50% less relevant and 39 data or 54.90% not relevant. Then the data obtained for practice questions as much as 429 with 66 data or 15.38% according to 48 practice questions in 1st semester and 18 practice questions in 2nd semester relevant, 30 data or 7.00% less relevant and 333 data or 77.62% not relevant.The results showed that the material and practice questions in the Kursbuch Netzwerk A1 book were not all or only a small part is compatible with the Core Competencies and Basic Competencies of 10th grade class because the book is a wider range of themes and materials, as well as the practice questions for 10th grade students.